Development of the INDEEP-MOODLE Model: An Innovative Deep Learning–Integrated Training Framework to Enhance Teachers’ Pedagogical Competence - Yari Dwikurnaningsih; Sophia Tri Satyawati (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2026)
This study aims to develop a MOODLE-based training model for innovative learning integrated with deep learning to enhance teachers’ teaching abilities. This research employed the Borg and Gall research and development (R&D) model up to the expert validation stage. The participants consisted of five school principals and twenty teachers. Data were collected through interviews, open-ended and closed-ended questionnaires, and focus group discussions. Qualitative data were analyzed using the Miles and Huberman model, while quantitative data were analyzed using descriptive statistical techniques, including percentages, categories, and mean scores. During the Research and Information Collecting phase, the findings indicated that teachers’ ability to implement innovative learning methods integrated with deep learning was categorized as sufficient, highlighting the need for further improvement. The developed training model is an online training program based on the MOODLE learning management system. The model consists of a visual representation and a detailed description outlining the concept of online training for innovative learning integrated with deep learning. Based on the validation conducted by four experts in content, technology, and instructional design, the conceptual model was rated very good, with an average score of 4.2. This result indicates that the model is valid and feasible to be further developed into a procedural training model to improve teachers' pedagogical competence. This study implies that technology-supported professional development models, such as INDEEP-MOODLE, provide a structured, sustainable, and scalable alternative to conventional workshop-based training for integrating innovative and deep learning principles into teachers’ pedagogical practices.